Prevention of Adolescent Pregnancy in Anglophone Sub-Saharan Africa: A Scoping Review of National Policies - Bright Opoku Ahinkorah; Melissa Kang; Lin Perry; Fiona Brooks (Kerman University of Medical Sciences, 2022)
BackgroundDespite the existence of preventive policies across sub-Saharan Africa, countries within the sub-region lead global rankings for rates of adolescent pregnancy. The aim of this scoping review was to identify and review national policies on the prevention of adolescent pregnancy in Anglophone sub-Saharan Africa. MethodsRelevant policies were identified from searches of national government websites and the search engine Google. Recognised screening and data extraction processes were used; data were subjected to content analysis using a published Framework for Evaluating Program and Policy Design on Adolescent Reproductive Health. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) extension for scoping reviews guidelines was used in reporting the review. ResultsIn line with the inclusion criteria that guided the selection of relevant policies in this study, 17 of 75 national policies were suitable for the analysis. All were backed by political recognition, were government and public initiatives, acknowledged a range of determinants of adolescent pregnancy and allocated human resources to policy activities. Few specified financial resourcing. Most policies acknowledged the importance of coordination and collaboration among public and private actors. All policies had objectives that addressed adolescent pregnancy but none were measurable or included timeframes. Provision of comprehensive sexuality education and adolescent reproductive health services were the most common recommendations. Monitoring and evaluation plans were present in all the policies. However, youth involvement in policy formulation, and plans for implementation, monitoring and evaluation was scarce. ConclusionOverall, national policy strengths were seen in relation to their political recognition, and all aspects of policy formulation. Policy implementation strengths and weaknesses were identified, the latter in relation to clear descriptions of financial resources. Importantly, the absence of measurable and time-bound objectives or formal evaluation of policy effectiveness confounds demonstration of what has been delivered and achieved. Youth involvement was notably absent in many policies. For future policy-setting, governments and policy-makers should make efforts to engage young people in policy development and to be transparent, realistic and address the necessary financial resourcing. They should set quantifiable policy objectives that provide a basis for assessing the adoption, uptake and effectiveness of policies in relation to measurable objectives.